Evaluation of energy saving measures implementation for the hot water supply system in Vladivostok airport - Irina A. Zhurmilova; Elena V. Tarasova; Evgeny A. Zyryanov (Архитектура, строительство, транспорт)
Implementing economically viable energy-saving measures is a priority for any large enterprises.Hot water supply system as one of the major heat consumers in airports offer significant potential for energy consumption reduction. Electric boilers are the primary heat source for the hot water system of the Vladivostok airport. To reduce energy consumption, the application of solar collectors for water heating and the installation of exhaust air heat recovery systems were considered. To evaluate the effectiveness of these energy-saving measures for the airport’s hot water system, theoretical calculations of water and heat consumption for domestic hot water were performed, and these were compared with actual values obtained from heat meter data. Based on these data, the actual average daily hot water consumption over 4 months was 6.68 m3/day, with an average passenger flow of 258 passengers per hour. The theoretical consumption for the same passenger flow was 6.83 m3/day. At a design passengers flow of 1.360 people per hour, the average daily water consumption was calculated to be 13.92 m3/day. The study calculated the key indicators of implementing the energy-saving measures at the design value of passenger flow. Supplying domestic hot water using exhaust air heat recovery has a simple payback period of 6.81 years; a payback period of solar hot water system comprising 86 solar collectors is 11.2 years.